Open letter to prime minister David Cameron and health secretary Andrew Lansley. (16th November 2010) - Nicholl, David J; Hilton-Jones, David; Palace,, Jacqueline; Richmond, Sam; Finlayson, Sarah; Winer, John; Weir, Andrew; Maddison, Paul; Fletcher, Nick; Sussman, Jon; Silver, Nick; Nixon, John; et al.
Abstract : Neurologists and paediatricians call for action on "massive" rises in the prices of orphan drugs